WORKSHOP PENYUSUNAN KISI-KISI SOAL DAN ANALISIS BUTIR SOAL DI SMP NEGERI TIAKUR - Mataheru, Wilmintjie; Huwaa, Novalin Calasin; Inuhan, Michael; Lekitoo, john Nandito (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2024)
In order to improve the quality of question preparation, service activities were carried out in the form of workshops on preparing question grids and analyzing question items. This activity was carried out at SMP Negeri Tiakur, with the target audience being teachers at that school. The achievement of implementing activities is measured by creating a participant satisfaction questionnaire. From the results of the satisfaction questionnaire analysis, very good results were obtained with an average percentage of 97.14%.